From Novice to Designer: Evaluating the Effectiveness of Canva Training-Workshops for Elementary Teachers in Buenavista, Guimaras, Philippines - Ga, James Ryan B.; Gallos, Loveson C.; Garcia, John Paul M.; Garmay, Beverly F.; Forca, Adrian J. (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2025)
In today’s increasingly digital world, education is undergoing a significant transformation. Traditional teaching methods are being supplemented and, in some cases, replaced by innovative tools that promote more interactive and engaging learning experiences. However, in many rural and underserved areas, access to such resources remains limited. Teachers of four Elementary Schools in Buenavista, Guimaras faced the dual challenge of navigating limited digital infrastructure and the increasing demand to incorporate technology into their teaching practices. In addressing the challenge, a comprehensive training-workshop on the use of Canva, empowering teachers to create visually engaging and interactive learning materials was conducted using the Pre and Post Self-Assessment. Results revealed that 23 of 56 participants rated themselves to have No Knowledge or Skills and after the community service, the notable results manifest the none of the participants remain to have No Knowledge or Skills rather, 27 of 56 participants elevated to have Fair Knowledge or Skills in using the Canva Platform as Educational Technology. This result is evident that the Community of Educators continues to strive for the betterment of the Educational Landscape of the Nation.